See It Grow: A randomized evaluation of digital innovations in crop insurance to increase insurance and fertilizer demand in Kenya - Kramer, Berber; Cecchi, Francesco; Kivuva, Benjamin; Waweru, Carol; Waithaka, Lilian (AgEcon, 2024)
Picture-based insurance (PBI) is an innovation designed to lower basis risk in index-based crop insurance for smallholder farmers by indemnifying insurance claims based on crop damage documented through a stream of pre- and post-damage smartphone pictures. To evaluate its impacts on insurance take-up and fertilizer use, we implemented a cluster randomized controlled trial in seven counties in Kenya. Approximately 190 villages are randomly assigned to a control group, as well as weather index-based insurance (WBI) and picture-based insurance (PBI) treatment arms, where farmers are offered free insurance trials of a standard rainfall insurance product and a similarly priced PBI product, respectively. Subsequently, farmers in these insurance treatment arms can purchase the insurance product of which they received a trial at subsidized premiums, whereas farmers in the control group are offered a standard insurance product at commercial premiums. PBI increases insurance take-up compared to WBI, especially among female farmers and those farming Arid and Semi-Arid Lands (ASALs). Both treatments increase fertilizer use compared to the control group, but this effect is most pronounced in the WBI treatment. The indemnity-based nature of PBI may disincentivize farmers to invest in crop management. We conclude that digital innovations in crop insurance that indemnity insurance claims based on visible crop losses can boost demand and have positive impacts on agricultural technology adoption, but insurance providers introducing such innovations will need to keep monitoring and managing moral hazard concerns.